European Regional Space Classification Regarding Smart Growth Level - Markowska, Małgorzata; Strahl, Danuta (Comparative Economic Research. Central and Eastern Europe, 2013)
Europe 2020 strategy, as the successor of Lisbon strategy, represents the vision of social market economy for Europe of the 21st century covering three related priorities: 1/ smart growth: knowledge based economy and innovation growth; 2/ sustainable growth: support for effective and taking advantage of resources economy which is more environmentally friendly and more competitive; 3/ inclusive growth: support for high employment level economy providing social and territorial cohesion. The paper presented classification results including European regional space positional statistics regarding advancement and smart growth level in NUTS 2 regions. Regional smart growth covers three pillars: innovation, creativity (Knowledge Based Economy) and smart specialization illustrated by characteristics available in Eurostat data resources. These qualities constituted the basis for constructing aggregate measures for specific pillars and also for the purposes of regional classification. The results of obtained classes were assessed in an overall European space, in groups of regions distinguished in line with integration processes chronology and also in capital regions and these including the country capital, as well as in the system of Polish regions.